School-Based Prevention–Oriented Socialization as a Strategy for Preventing Verbal Bullying: A Community Engagement Study at SDN 06 Nagari Sumanik - Dasmi, Misa; Darti, Mila (Mangabdi: Journal of Community Engagement in Religion, Social, and Humanities, 2025)
Verbal bullying remains a prevalent issue in student interactions at SDN 06 Nagari Sumanik, occurring both in classroom settings and across the broader school environment. This condition prompted the implementation of a community engagement program in the form of School-Based Prevention–oriented socialization aimed at preventing verbal bullying from an early age. The program sought to enhance elementary school students’ understanding and awareness of the risks and consequences of verbal bullying while fostering a safe and supportive school climate. The activity employed a participatory educational approach conducted through three stages: planning, implementation, and monitoring. Data were collected through observation, interactive discussions, and assessments of students’ understanding before and after the intervention. The socialization activities included structured material delivery, educational video screenings, ice-breaking sessions, and question-and-answer discussions. The results indicate an improvement in students’ comprehension of the forms, impacts, and prevention of verbal bullying, as reflected in increased active participation and students’ ability to identify bullying behaviors. Overall, the program positively influenced students’ interaction patterns and demonstrates that the School-Based Prevention approach is an effective preventive strategy for reducing verbal bullying practices in elementary school settings.